STUDI DRAMATURGI SALES MODEL DI KOMUNITAS FOTOGRAFER 2016 DI JAKARTA - Imam Nuraryo (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2018)
The researcher aims to know the Study of Dramatugy of Sales Model in Photographer Community 2016 in Jakarta. This research will be done to see how the front stage, center stage and backstage of a Sales Model using a dramatic study approach.Â This study uses dramaturgy theory that explores the front side of the stage where there are personalized settings and fronts that include the appearance and style, the middle-stage side where the Sales Model prepares itself to appear on the front stage and backstage of an actor. In the dramaturgy study will be seen about the difference in actor behavior when in front stage, middle stage and backstage.Key words: dramaturgy, sales model, community, photograferÂ